Exposure to 2, 3, 7, 8-tetrachlorodibenzo-paradioxin (TCDD) hampers the host defense capability of a bivalve species, Tegillarca granosa. Issue 86 (March 2019) - Zha, Shanjie; Shi, Wei; Su, Wenhao; Guan, Xiaofan; Liu, Guangxu
Abstract: Though increasing reports of deleterious impacts of dioxins and polychlorinated biphenyls (PCBs) on a variety of marine organisms have been described, their effects on the host defense capability of marine bivalve mollusks remain poorly understood. In the present study we used 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD) as a representative of dioxins and PCBs to investigate its impacts on the host defense capability of the blood clam, Tegillarca granosa . After exposure of clams to a range (0, 0.01, 0.1, 1, and 10 μg/L) of TCDD for 96 h, the total count, cell type composition, and phagocytic rate of haemocytes were analyzed. In addition, alkaline phosphatase (ALP) activity, cell viability, and the extent of DNA damage of haemocytes were also investigated. Our results showed that exposure to relatively high TCDD concentrations led to significant reductions in the total count and phagocytic activity of haemocytes, which could be accounted by aggravated DNA damage and reduced cell viability. In addition, the percentage of red granulocyte was significantly decreased whereas that of basophil granulocyte was significantly increased upon high doses TCDD exposure (effective concentrations are 1 μg/L and 10 μg/L for red and basophil granulocytes, respectively). Moreover, clams exposed to TCDD had a significant higher activity of ALP, may also indicate an enhanced ability to eliminate pathogens through direct dephosphorylation process whereas a suppressed inflammatory response through indirect regulating of downstream molecular cascade reaction. These findings suggest that TCDD may hamper the host defense capability and therefore render bivalve mollusks more vulnerable to pathogen infections. Highlights: TCDD exposure induced a reduction in total haemocytes counts and phagocytosis. TCDD exposure caused significant reduction in cell viability whereas aggravation in DNA damage of haemocytes. Clams exposed to TCDD had a significant higher activity of ALP.